2002
DOI: 10.1128/cdli.9.4.846-851.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Molecular Cloning, and Evaluation of Potential Use of Isocitrate Dehydrogenase II of Mycobacterium bovis BCG in Serodiagnosis of Tuberculosis

Abstract: Diagnosis of tuberculosis is time-consuming and requires infrastructures which are often not available in countries with high incidences of the disease. In the present study, an 82-kDa protein antigen was isolated by affinity chromatography and was identified by peptide mass fingerprinting as isocitrate dehydrogenase II, which is encoded by the icd2 gene of Mycobacterium bovis BCG. The icd2 gene of BCG was cloned by PCR, and the product of recombinant gene expression was purified and analyzed by two-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Its homologous protein was identified as antigen of pathogenic fungus A. fumigatus (Singh et al 2010) and Gram-negative bacterium Helicobacter pylori (Mcatee et al 1998). Idh2p was also shown to elicit strong B cell response and was a potential immune marker for serodiagnosis of tuberculosis (Florio et al 2002). Importantly, this study showed that the recombinant Idh2p reacted specifically with pooled sera from mice infected with C. parapsilosis on immunoblot, therefore validating its antigenicity.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Its homologous protein was identified as antigen of pathogenic fungus A. fumigatus (Singh et al 2010) and Gram-negative bacterium Helicobacter pylori (Mcatee et al 1998). Idh2p was also shown to elicit strong B cell response and was a potential immune marker for serodiagnosis of tuberculosis (Florio et al 2002). Importantly, this study showed that the recombinant Idh2p reacted specifically with pooled sera from mice infected with C. parapsilosis on immunoblot, therefore validating its antigenicity.…”
Section: Discussionsupporting
confidence: 58%
“…Idh2p was also shown to elicit strong B cell response and was a potential immune marker for serodiagnosis of tuberculosis (Florio et al . ). Importantly, this study showed that the recombinant Idh2p reacted specifically with pooled sera from mice infected with C. parapsilosis on immunoblot, therefore validating its antigenicity.…”
Section: Discussionmentioning
confidence: 97%
“…Many TCA cycle and related enzymes in Mtb have been studied individually in recent years, such as isocitrate lyase (8), malate dehydrogenase (26), and isocitrate dehydrogenase (26,27). However, to our knowledge, there have been no reports in which KDH activity was purified from Mtb lysates or reconstituted by using recombinant Mtb proteins.…”
Section: Discussionmentioning
confidence: 89%
“…The picture remained unaltered when we used PPD in place of Hsp10. It is pertinent to note that although several antigens have been tested for use in serodiagnosis, no test with a single antigen has proved able to achieve sensitivity and specificity in a study population that is suitably large and heterogeneous (3,5,9,11,13,14,16,17,18,19,21,22). The factors responsible for this include (i) the stage of the disease, (ii) the location of the infection, and (iii) the genetic background.…”
Section: Discussionmentioning
confidence: 99%